Characteristics of female mentally disordered offenders culpable under the new legislation in Japan: A gender comparison study. (10th March 2015) - Nagata, Takako; Nakagawa, Atsuo; Matsumoto, Satoko; Shiina, Akihiro; Iyo, Masaomi; Hirabayashi, Naotsugu; Igarashi, Yoshito
Abstract: Background: Although a substantial increase in the number of female offenders has drawn interest towards understanding their unique characteristics, few studies have investigated the characteristics of female mentally disordered offenders in Japan and none since the legislation enacted in 2005 in Japan, which provided for special services for them. Aims: The aim of this study is to identify those characteristics of people detained under this legislation, which distinguish the women from the men and may indicate special needs among the women. Methods: A retrospective records‐based study of all patients admitted to one secure unit in the 8 years since its opening in July 2005 until a census date of 31 October 2013. Results: Thirty‐six (15%) of the patients were women. Marriage, mood disorders, past suicide attempts and homicide were more common among the women than the men. Six of the female offender‐patients had committed filicides, of which four were infanticides. Conclusion: There appears to be a particularly vulnerable sub‐group of women with severe mood disorders, a history of serious suicide attempts and young children at risk of harming those children. Our sample was small and from a single unit so, given the potential importance of improving understanding of who is at risk in such circumstances, extending our study nationally seems indicated. Copyright © 2015 John Wiley & Sons, Ltd.